Interlayer bonding characterization of interfaces reinforced with geocomposites in field applications. Issue 1 (February 2022) - Canestrari, F.; Cardone, F.; Gaudenzi, E.; Chiola, D.; Gasbarro, N.; Ferrotti, G.
Abstract: Geocomposites are extensively used in asphalt pavements as they provide significant long-term pavement benefits. Indeed, when correctly installed, geocomposites enhance road pavement performance thanks to their waterproofing properties, stress absorbing membrane interlayer (SAMI) action and improved mechanical strength of the pavement. Nevertheless, the presence of an interlayer causes de-bonding effects that negatively influence the overall pavement characteristics. This paper presents an experimental investigation aimed at comparing the interlayer bonding characteristics of four different geocomposites with an unreinforced reference configuration, laid on an Italian motorway section, in which the reinforcement depth and the lower layer surface condition (milled or new) were also varied. Interlayer shear strength (ISS) was measured, on both cores and laboratory produced specimens, through Leutner and Ancona Shear Testing Research and Analysis (ASTRA) equipment. The ISS results showed that geocomposites can be successfully applied directly on milled surfaces. Moreover, the application of a normal stress, as in the ASTRA device, tends to mitigate any difference related to the specimen heterogeneity. Finally, existing laws, which correlate the results obtained with different shear equipment on unreinforced interfaces, were generalized by considering the presence of geocomposites and the corresponding ISS specification limits were proposed for both ASTRA and Leutner test. Highlights: Interlayer bonding comparison between unreinforced and reinforced configuration. Field application of geocomposites at different depth and on new or milled surfaces. Determination of Interlayer Shear Strength through different shear test equipment. Generalization of laws correlating results obtained with different shear equipment.